The last word [videorecording (DVD)] - MacLaine, Shirley, 1934-; Seyfried, Amanda; Dixon, Annjewel Lee (Universal Pictures Home Entertainment, 2017)
Harriet is a retired businesswoman who tries to control everything around her. When she decides to write her own obituary, a young journalist takes up the task of finding out the truth, resulting in a life-altering friendship.